PHYTOCHEMICAL SCREENING AND GAS CHROMATOGRAPHY-MASS SPECTROSCOPY ANALYSIS OF BIOACTIVE COMPOUNDS AND BIOSYNTHESIS OF SILVER NANOPARTICLES USING SPROUT EXTRACTS OF VIGNA RADIATA L. AND THEIR ANTIOXIDANT AND ANTIBACTERIAL ACTIVITY - T, SIVAKUMAR (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: The present study was aimed to investigate the facile synthesis of silver nanoparticles (AgNPs) using the green gram sprout extract (GGSE) of Vigna radiata L. and also in vitro studies of antioxidant and antimicrobial activities. Methods: Gas chromatography-mass spectroscopy techniques have been used for the qualitative and quantitative evaluation of the phytochemicals present in the green gram seedlings. The antioxidant activity of AgNPs and GGSE was analyzed using the 1,1-diphenyl-2-picrylhydrazyl (DPPH) assay. In vitro antibacterial activity was performed using the agar well diffusion method. Results: The presence of various secondary metabolites such as flavonoids, steroids, terpenoids, alkaloids, amino acids, polyphenol, glycoside, and protein was found in samples. The major chemical compounds of V. radiata were n-hexadecanoic acid, stigmasterol, caffeine, hexadecanoic acid, cholest-5-en-3-ol (3.beta.)-, and cyclopentane. The percentage of DPPH activity was enhanced on increasing the concentration of AgNPs. In vitro antibacterial effect of the diverse concentrations of AgNPs was investigated against each Gram-negative (Klebsiella aerogenes, and Escherichia coli) and Gram-positive (Bacillus substilis and Staphylococcus aureus) bacterial strains. Conclusion: The result suggests that biosynthesized AgNPs have good antibacterial and antioxidant activity and might be a potential for the bioactive components.